In Silico Approach of Flavonol in Hibiscus sabdariffa as Proteasome Inhibitors Targeting the Ubiquitin-Proteasome Pathway - Choironi, Nur Amalia; Prameswari, Syakhsiyatunnisa Galuh; Baroroh, Hanif Nasiatul (Chimica et Natura Acta, 2025)
Multiple myeloma is a blood cancer characterized by the abnormal proliferation of B cells that accumulate in the bone marrow. The proliferation of these cells depends on the role of the proteasome through the ubiquitin-proteasome pathway to degrade proteins that regulate the cell cycle, apoptosis, and stress response. The proteasome is the main target of proteasome inhibitors for the treatment of multiple myeloma. Flavonoid compounds in Hibiscus sabdariffa flowers, such as isoquercitrin, quercitrin, quercetagetin, isorhamnetin, and astragalin, have the potential to act as proteasome inhibitors. The insilico study aims to determine the potential of these compounds as proteasome inhibitors based on the results of molecular docking and molecular dynamics simulation. Molecular docking was performed using AutoDock Vina, PyMol, and BIOVIA Discovery Studio. The best compounds from the docking results were then tested for interaction stability through molecular dynamics using YASARA software. Quercetagetin, isoquercitrin, and isohamnetin, based on the results of molecular docking, have the lowest binding affinity of -6.0, -5.7, and -5.5 kcal/mol, respectively. The three compounds bind to the active site of the 20S proteasome, namely Thr1, Ala20, Thr21, and Ala49. The RMSD values in the molecular dynamics of quercetagetin (1.290 Å), isorhamnetin (1.839 Å), and carfilzomib (1.843 Å). The binding affinity of quercetagetin (-422.623 kJ/mol), isorhamnetin (-438.388 kJ/mol), and carfilzomib (664.956 kJ/mol). Molecular docking and molecular dynamics findings indicate that isorhamnetin binds to the amino acid residues Thr1 and Ala49, which are the active sites of the 20S proteasome.